Inequality in Five Countries in the 1980 s: The Role of Demographic Shifts, Markets and Government Policies - Markus Jäntti (Luxembourg Income Study (LIS), 1996)
Using LIS data, Jäntti examines levels and trends in income inequality among families in five industrialized countries, namely Canada, the Netherlands, Sweden, the United Kingdom, and the United States, exploring the possibility that markets, the public sector or demographic shifts would account for changes. Inequality increased in Sweden, the United Kingdom, and the United States, but did not increase in Canada and the Netherlands. He finds that earnings account for much of the observed increase in income inequality, partly due to increased inequality of head's earnings and partly because of an increased share of spouse's earnings in household income. The public sector can, in general, be assigned a moderating effect on these changes. Demographic shifts cannot be assigned any major role in the increase in inequality.
Keywords: 330; Einkommensverteilung; Großbritannien; Kanada; Niederlande; Schweden; USA